Development of nested polymerase chain reaction for detection of rabies - Fazilah Muhamad Alwi; Musherah Khusaini; Ag. Muhammad Sagaf Abu Bakar; Ainol Azifa Mohd Faik (IOP Publishing Ltd., 2022)
Rabies is an acute progressive and zoonotic disease which is caused by the rabies virus. Rabies virus is the prototype virus belonging to the genus lyssavirus in the family Rhabdoviridae of the order Mononegavirales. The aim of this study was to develop a nested reverse-transcriptase polymerase chain reaction (nRTPCR) for the detection of this virus along with a canine internal control to monitor the integrity of the extracted RNA. A pair of outer and inner primer targeting the N gene of the virus was evaluated along with β-actin gene as the internal control. This nRTPCR can detect up to 20 viral copy number.